Potential inhibition of pro-inflammatory mediators by Ficus deltoidea jack leaves aqueous extract in lipopolysaccharide-induced microglial cells - Zolkiffly, Siti Zaidathul Iman (2021)
To date, Alzheimer’s disease (AD) is responsible for the majority of dementia cases among the elderly population around the globe. Neuroinflammation and oxidative stress are among the fundamental factors that lead to the progression of the disease. Recently, there has been a resurgence of interest in implementing natural products to slow the progression of AD due to their enhanced therapeutic benefits when compared to available synthetic drugs. Ficus deltoidea (FD), also known as “Mas cotek”, is widely consumed in traditional medicine as a treatment to various ailments in Malaysia. Among the many types of bioactive compounds, vitexin and isovitexin are abundantly found in the leaves of FD that possessed many pharmacological properties including neuroprotection. Nonetheless, its effects on key events in neuroinflammation are unknown. In this study, FD aqueous extract was investigated for its potential anti-neuroinflammatory and antioxidant properties on lipopolysaccharide-induced microglial cells by assessing the level of pro-inflammatory and cytotoxic factors. FD aqueous extract was prepared and freeze dried prior to use in in vitro study. Quantification of vitexin and isovitexin in the extract was carried out using high performance liquid chromatography (HPLC). In silico test was performed to predict the effectiveness of the ligand molecules of both vitexin and isovitexin to penetrate through the blood-brain barrier (BBB). The extract was evaluated for its cytotoxicity activity via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Pre-treatment with the extract on lipopolysaccharide (LPS)-induced microglial cells was done to determine its anti-neuroinflammatory and antioxidant properties by measuring the level of reactive oxygen species (ROS), nitric oxide (NO), tumour necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) via 2′-7′-dichlorofluorescin diacetate (DCFDA) assay, Griess assay and Western blot respectively. The result showed that the extract at tested concentrations (0.1, 1, 10, 100 μg/mL) were not cytotoxic as the percentage cell viability were above ~80%. At the highest concentration (100 μg/mL), the extract significantly reduced the production of ROS, NO, TNF-α, IL 1β and IL-6 in microglial cells induced by LPS. From this study, the extract demonstrated neuroprotective effects by attenuating the production of proinflammatory and cytotoxic factors in LPS-induced microglial cells, possibly by mediating the nuclear factor-kappa B (NF-κB) signalling pathway.